(3cJGH GdTWQfLs - (3eMeO TcQj , eMeO TcQj Gdecj,J (B1333 (3g` s
(3ChdgG (B:s
(3GdebOeI ai EHGMI GddYH HGdTWQfL hPcQ eG jSJOd Hg Ydi Pdc ef GdHQGgjf GdhGVMI s
(3BNQgG (B:s
(3hgh NjQ ef HjOb GdTGI hGdajd fehPL s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B159s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3CdYGH JjehQ (B12) s
Keywords: (3GdTWQfLs